2018
DOI: 10.4081/monaldi.2018.988
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender in cardiovascular medicine: Lessons from the gender/sex-issue in heart failure

Abstract: Heart Failure (HF) is a major healthcare issue, given its high prevalence and incidence, the rate of comorbidities, the related high health-care costs and its poor outcome. In the last years mounting evidence revealed several differences between men and women affected by this clinical condition. Apart from the well-known difference in phenotype (HF with reduced ejection fraction (HFrEF) occurs more commonly in men, and HF with preserved ejection fraction (HFpEF) is more frequent in women) other relevant sex-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
(75 reference statements)
3
9
0
Order By: Relevance
“…However, women have been historically included in a smaller proportion (around 30%) than men in clinical trials, and their therapeutic management and prognosis have been less studied. All this leads to a lower prescription in women of the treatments recommended by clinical practice guidelines [12,31,[40][41][42] and, for reasons not entirely clear, with lower average drug doses [9,[43][44][45]. Although information on drug doses used and on the LVEF of our patients were not available in our cohort, we confirmed, in general, the lower prescription of the specific treatments for HF in women.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, women have been historically included in a smaller proportion (around 30%) than men in clinical trials, and their therapeutic management and prognosis have been less studied. All this leads to a lower prescription in women of the treatments recommended by clinical practice guidelines [12,31,[40][41][42] and, for reasons not entirely clear, with lower average drug doses [9,[43][44][45]. Although information on drug doses used and on the LVEF of our patients were not available in our cohort, we confirmed, in general, the lower prescription of the specific treatments for HF in women.…”
Section: Discussionsupporting
confidence: 75%
“…The higher prevalence of ischemic heart disease and arrhythmias in men would justify the greater dispensation of anti-coagulation and anti-aggregation treatments, in line with the results of Dewan et al [26], who also found a greater use of statins [6,41]. In other studies, greater side-effects related to ACE inhibitors have been reported for women, such as cough or angioedema [5,43,46,47]. In our sample, women had less arrhythmia and were also treated more frequently with digoxin than with beta-blockers, despite the greater association in women between use of digoxin and mortality and/or negative adverse effects [12,48,49].…”
Section: Discussionmentioning
confidence: 70%
“…These differences might be attributed to the HF aetiology, left ventricular ejection fraction (HFrEF vs. HFpEF), and New York Health Association classifications, which were not available in this dataset. Women have a higher incidence of HF at older age, have more HFpEF, and suffer more from obesity, diabetes, and hypertension, while man have a higher incidence at a younger age with more HFrEF due to ischaemic aetiology 24 . Furthermore, women generally live longer than men.…”
Section: Discussionmentioning
confidence: 99%
“…Women have a higher incidence of HF at older age, have more HFpEF, and suffer more from obesity, diabetes, and hypertension, while man have a higher incidence at a younger age with more HFrEF due to ischaemic aetiology. 24 Furthermore, women generally live longer than men. In our study, women with RI, COPD/ asthma, and diabetes had a worse prognosis, even though prevalence of RI was not significantly different, and COPD/asthma and diabetes were more common among men.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…In adult patients, several studies have already demonstrated sex related differences in cardio-circulation (12)(13)(14). Sex related differences concerning pathophysiology, clinical features and therapy are more and more in the focus of research, since these differences may have an impact on clinical practice.…”
Section: Sex Related Difference In Cardiac Output During Neonatal Transition In Term Neonatesmentioning
confidence: 99%